Optimalization Design of User Services in E-Government Waste Management Apps - Alfi, Firmansyah Yuni; Singagerda, Faurani Santi; Muludi, Kurnia; Meizari, Ary (Prosiding International conference on Information Technology and Business (ICITB), 2023)
This study aimed to address Indonesia's critical environmental issue of waste management by designing optimal user services for an eGovernment waste management application. The research is exploratory in nature, employing a combination of qualitative and quantitative methods to develop an integrated digital solution. Our methodology includes data analysis from World Bank reports, insights from the Ocean Conservancy, and the examination of government policies and advanced technological applications. The results demonstrated the urgent need for efficient waste management systems, as Indonesia is the second-largest contributor to oceanic plastic waste. We propose a framework for an e-Government application that leverages Internet of Things (IoT), big data, and digital platforms to monitor, manage, and optimize waste management processes, enhancing transparency and effectiveness. Our findings suggested that the application's user-centric design significantly improves community engagement and participation in sustainable waste practices. The implications of this research point towards a scalable and sustainable model for waste management that can be adopted by other regions facing similar challenges. We recommend further development of the application with a focus on user feedback and iterative design to ensure adaptability to diverse waste management contexts. The contribution of this study lies in its potential to revolutionize waste management practices through digital transformation, providing a blueprint for environmental sustainability initiatives within e-Government frameworks.Â Keywords: waste management, digital transformation, E-Government Applications, sustainability, user services